Oligomeric amyloid-beta induces MAPK-mediated activation of brain cytosolic and calcium-independent phospholipase A(2) in a spatial-specific manner - Palavicini, Juan Pablo (Acta Neuropathol Commun, 2017)
Alzheimer’s disease (AD) is histopathologically characterized by the build-up of fibrillar amyloid beta (Aβ) in the form of amyloid plaques and the development of intraneuronal neurofibrillary tangles consisting of aggregated hyperphosphorylated Tau. Although amyloid fibrils were originally considered responsible for AD pathogenesis, recent convincing evidence strongly implicates soluble oligomeric Aβ as the primary neurotoxic species driving disease progression. A third largely ignored pathological hallmark, originally described by Alois Alzheimer, is the presence of “adipose inclusions”, suggestive of aberrant lipid metabolism. The molecular mechanisms underlying these “lipoid granules”, as well as their potential link to soluble and/or fibrillar Aβ remain largely unknown. Seeking to better-understand these conundrums, we took advantage of the powerful technology of multidimensional mass spectrometry-based shotgun lipidomics and an AD transgenic mouse model overexpressing mutant amyloid precursor protein (APP E693Δ-Osaka-), where AD-like pathology and neurodegeneration occur as a consequence of oligomeric Aβ accumulation in the absence of amyloid plaques. Our results revealed for the first time that APP overexpression and oligomeric Aβ accumulation lead to an additive global accumulation of nonesterified polyunsaturated fatty acids (PUFAs) independently of amyloid plaques. Furthermore, we revealed that this accumulation is mediated by an increase in phospholipase A(2) (PLA(2)) activity, evidenced by an accumulation of sn-1 lysophosphatidylcholine and by MAPK-mediated phosphorylation/activation of group IV Ca(2+)-dependent cytosolic (cPLA(2)) and the group VI Ca(2+)-independent PLA(2) (iPLA(2)) independently of PKC. We further revealed that Aβ-induced oxidative stress also disrupts lipid metabolism via reactive oxygen species-mediated phospholipid cleavage leading to increased sn-2 lysophosphatidylcholine as well as lipid peroxidation and the subsequent accumulation of 4-hydroxynonenal. Brain histological studies implicated cPLA(2) activity with arachidonic acid accumulation within myelin-rich regions, and iPLA(2) activity with docosahexaenoic acid accumulation within pyramidal neuron-rich regions. Taken together, our results suggest that PLA(2)-mediated accumulation of free PUFAs drives AD-related disruption of brain lipid metabolism.